2015
DOI: 10.1007/s00339-015-9058-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Heusler single crystals examined by depth-dependent positron annihilation techniques

Abstract: Abstract.Heusler compounds exhibit a wide range of different electronic ground states and are hence expected to be applicable as functional materials in novel electronic and spintronic devices. Since the growth of large and defect-free Heusler crystals is still challenging, single crystals of Fe 2 TiSn and Cu 2 MnAl were grown by the optical floating zone technique. Two positron annihilation techniques -Angular Correlation of Annihilation Radiation (ACAR) and Doppler Broadening Spectroscopy (DBS) -were applied… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…This is in good agreement with previously published values [25][26][27][28]. Complementary positron annihilation experiments performed on our sample revealed that the vacancy density is below 9.7 × 10 −5 per atom [29].…”
supporting
confidence: 93%
See 2 more Smart Citations
“…This is in good agreement with previously published values [25][26][27][28]. Complementary positron annihilation experiments performed on our sample revealed that the vacancy density is below 9.7 × 10 −5 per atom [29].…”
supporting
confidence: 93%
“…Complementary positron annihilation experiments performed on our sample revealed that the vacancy density is below 9.7 × 10 −5 per atom [29].…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…For the present study, we used the CDB spectrometer [16] with a monoenergetic positron beam provided by the neutron induced positron source Munich (NEPOMUC) [17] at the research neutron source Heinz-Maier Leibnitz (FRM II). DBS at this spectrometer with an accessible temperature range of 40 − 1100 K was shown to be particularly suited for the determination of the vacancy concentration, e.g., in Heusler alloys [18] or the in-situ observation of fast defect annealing after severe plastic deformation [19]. In addition, compared to conventional PAS with β + emitters the usage of a positron beam has the advantage of simple sample heating under ultra high vacuum conditions and that the recorded signal exclusively stems from annihilation events inside the sample (absence of the so-called source component).…”
mentioning
confidence: 99%
“…Monoenergetic positron beams allow for depth-dependent defect investigations of samples or thin layers. The positron diffusion length can be measured by variation of the implantation energy that in turn allows to evaluate high vacancy concentrations up to the percent range [16]. DBS with energy variable positron beams is particularly suited to investigate the depth distribution of defects.…”
Section: Introductionmentioning
confidence: 99%